From Green Product to Green Reputatuin: An Analysis of How Word of Mouth and Innovation Shape A Brand's Sustainability Image - Ichwana, Salsabela Oktanur; Sanistasya, Poppy Alvianolita; Arsyad, Annisa Wahyuni; Hikmah, Mukhibatul (Proceedings International Conference on Education Innovation and Social Science, 2025)
These Technological advancement in the modern era has significantly transformed how people communicate, making it faster, more efficient, and more accessible. One sector that has experienced rapid growth due to this development is the smartphone industry. Intense competition among manufacturers has driven the emergence of various product innovations to meet consumer needs and preferences, including support for sustainability values. Xiaomi has become one of the leading brands in the Indonesian market by offering affordable pricing strategies through popular sub-brands such as Redmi and Poco. This study is grounded in the Triple Bottom Line theory and the concept of marketing communication as its theoretical framework. The research utilizes a quantitative method with an associative design. The sampling process applied purposive sampling, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS version 4.1.1.2. The findings demonstrate that all direct paths in the proposed model exert a positive and significant effect on Purchase Decisions. However, the indirect effects through Brand Image are not significant, indicating that Brand Image does not mediate the relationship between Word of Mouth and Green Product Innovatioan with Purchase Decisions. Therefore, product innovation and communication strategies should focus directly on influencing consumer Purchase Decisions.